Inércia de juros e regras de Taylor: Explorando as funç\~oes de resposta a impulso em um modelo de equilíbrio geral com parâmetros estilizados para o Brazil - Dionisio Dias Carneiro; Pedro Garcia Duarte (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2001)
– The fit of empirical Taylor Rules to Brazilian data improves if we consider the hypothesis of interest rate inertia. Inertia seems to be part of monetary policy of several countries and reflects the action of Central Banks of not adjusting once-for-all to changing conditions. This article extends the concept of inertia considered by Duarte (2001) in the general intertemporal equilibrium model developed by Woodford (2000(b)), which corresponds to the monetary shock first-order autoregressive coefficient. We explore here the concept of inertia related to the presence of first lag of interest rate in the three Taylor rules examined in characterization of impulse response functions of variables to a monetary shock. The short run response of variables and the time it takes for their return to equilibrium depend more on the autoregressive coefficient of the shock than on the interest rate inertia. But this inertia is important when the Taylor Rule includes lagged inflation and output, because in this case, a smaller oscillation of the response of variables to shocks is obtained. It is also important in the case of forward looking Taylor Rule.
Keywords: E17; E47; E52; 330